International business research and scholarship in the Middle East: developments and future directions. Issue 3 (3rd July 2021) - Budhwar, Pawan; Pereira, Vijay; Temouri, Yama; Do, Hoa
Abstract: In this introduction we review the extant literature that demonstrate the importance of the Middle Eastern institutional and cultural context in shaping international business's (IB) strategies and practices across several countries. Drawing on the literature, as well as the five articles included in this special issue, we (1) outline the state of socio-cultural, historical and economic forces that shape international business in several Middle Eastern nations; (2) utilize institutional theory to evaluate the constraints of international business practices in the Middle East; and (3) highlight the key gaps in the literature and the challenges faced by IB scholars and practitioners in the Middle East. We subsequently propose an agenda for future research in order to lay the foundation for international business scholars to advance the theorizing and application of IB practices in the Middle East context.